Protection and preservation options for rubberwood sawn timber and finished products - Hong L T; Selamat S; Singh K D; Tam M K (In: Proceedings of the 2nd Rubberwood Seminar, 19-20 November 1985, Forest Research Institute of Malaysia, Kuala Lumpur, Malaysia, pp.49-63., 1985)
The conventional dipping method for the treatment of rubberwood will not be acceptable in the near future. Other optios of preservative treatment which provide long-term protection of rubberwood are given. Processes using aqueous preservatives such as copper-chrome-arsenic, borax, alkylammonium compounds, synthetic pyrethroids etc are discussed. The selection of any particular preservative process should relate to factors that are of prime importance to the cost of production and processing schedule so that effective and economical protection is obtained.
Keywords: Rubberwood